Pengaruh Pelatihan Mindfulness Service Terhadap Sikap Pelayanan Prima - Herwanti, S.Psi, Heidias (2016)
This experimental research attemped to describe the effect of mindfulness meditation training for behaviour of exxecelent service to the Academic Administration Biro staff Muhammadiyah University of Surakarta. The hypothesis of the study is training mindfulness service for subyek, has excellent service attitude different between the control group and experimental group. The experimental group more than high attitude excellent service value for kontrol group. In order to test hypothesis 42 subject were selected as the subjects. They were than devided into two group ; an experimental group consists of 21 subjects whom mindfulness meditation training heve been offered to them a control group consists of 21 subjects whom no treatment were presented them. The research data was obtained using the author mindfulness scale modification of mindfulness scale prepared by Azis (2007) and excellent service scale modificed from Arimawati (2007). Based on the results of statiscal test by using t-test, post test score between the experimental group and control group obtained the results of the t test value of t = 13,197, p = 0,010 < 0,05. These results prove there is a significant difference between the attitude of excellent service in the experimental group and the control group, in which the experimental group that received treatment showed increased mindfulness meditation training excellent service attitude than the control group. Based on the results so that it is advisable to Academic Administration Biro Staff who is the subject of mindfulness meditation training can do it continuously. Futhur research is recommended to conduct similar studies with some consider as a greather of subjects, a longer time and space or place of training and the provision of duty and mindfulness meditation training several times.